2022
DOI: 10.1155/2022/5120678
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Campylobacter coli and Campylobacter jejuni Isolated from Pig Guts, Pig Feces, and Surface Swabs from the Cutting Tables at Slaughterhouse and Taverns in Southern Benin

Abstract: Campylobacter food-borne infections are a serious public health problem. In Benin, there is a proliferation of pork consumption in several forms. This study aims to determine the prevalence and the antimicrobial resistance of Campylobacter coli and Campylobacter jejuni strains isolated from pig guts, pig feces, and surface swabs from the cutting tables in southern Benin. For this purpose, 200 samples of pig guts, 40 samples of swabs from the cutting table surface, and 8 samples of pig feces were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In the present study, all isolates detected from caecal samples were identified as C . coli , which is consistent with other similar studies [ 8 , 10 , 29 ]. Additionally, slaughterhouse studies in Latvia and Denmark revealed that ~90% of the pig-origin isolates were C .…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, all isolates detected from caecal samples were identified as C . coli , which is consistent with other similar studies [ 8 , 10 , 29 ]. Additionally, slaughterhouse studies in Latvia and Denmark revealed that ~90% of the pig-origin isolates were C .…”
Section: Discussionsupporting
confidence: 94%